Digging up Old Stories: How the Soviet Myths of Allied Intervention into the Russian North in 1918–1919 are used in the Context of Russia’s War in Ukraine. The Case of Mudyug Concentration Camp Museum - Golysheva , Natalia (Politologija, 2024)
The mythology of the foreign interference into the Russian civil war goes to the heart of the memory politics in Putin’s Russia today, most recently in connection with the invasion in Ukraine. In a bid to unite the country against perceived threats from the NATO alliance, the Russian leadership engages Soviet narratives going back to the Allied intervention into North Russia in 1918–1920, as a deterrent against association with the West. During Soviet times multiple memorials were created in the North to the victims of intervention in support of this narrative. Central to it was the Mudyug ‘concentration camp’ museum, established to demonstrate the atrocities of the intervention forces. Following the collapse of the Soviet Union this museum was branded as propaganda and eventually got decommissioned. Yet after Russia’s annexation of Crimea in 2014 and subsequent war with Ukraine, the old intervention narratives saw a comeback. Backed by the state, the local memory activists in Arkhangelsk in North Russia took to restoring the Mudyug camp museum as a forepost of patriotic tourism in the region.